In vitro Anti-Leishmanial Activities of Methanol Extract of Brucea antidysenterica J.F. Mill Seeds and Its Solvent Fractions - Ketema T; Tadele M; Gebrie Z; Makonnen E; Hailu A; Abay SM (Dove Medical Press, 2023)
Tasisa Ketema,1 Markos Tadele,2 Zewdie Gebrie,1 Eyasu Makonnen,1,3 Asrat Hailu,3,4 Solomon M Abay1 1Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Science, Addis Ababa University, Addis Ababa, Ethiopia; 2Animal Health Research Program, Ethiopian Institute of Agricultural Research, Holetta, Ethiopia; 3Center for Innovative Drug Development and Therapeutic Trials for Africa (CDT Africa), College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 4Department of Microbiology, Immunology and Parasitology, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Solomon M Abay, Department of Pharmacology and Clinical Pharmacy, Addis Ababa University, Zambia Street, P.O. Box 9086, Addis Ababa, Ethiopia, Tel +251 941 222169, Email Solomon.mequanente@aau.edu.etIntroduction: Leishmaniasis is one of the neglected tropical diseases, threatening lives of about 350 million people globally. Brucea antidysenterica seeds are used for the treatment of cutaneous leishmaniasis in the traditional medicine in Ethiopia.Objective: This study aimed to evaluate Brucea antidysenterica seeds' anti-leishmanial activity in vitro.Methods: The crude (80% methanol) extract of Brucea antidysenterica seeds and its fractions were evaluated for their anti-leishmanial activities against promastigotes and intracellular amastigotes of Leishmania donovani and Leishmania aethiopica, and for their cytotoxic effects against mammalian cells. The quantitative estimations of total phenolic compounds (TPCs), flavonoids (TFCs) and alkaloids (TACs) were determined, spectrophotometrically. Median inhibitory concentration (IC50) and median cytotoxic concentration (CC50) of the extract and its solvent fractions were calculated using GraphPad Prism 9.1.0 computer software. Data was presented as mean ± standard error of the mean (SEM).Results: The crude extract and its hexane, ethyl acetate and butanol fractions showed anti-leishmanial activities, with IC50 values of 4.14- 60.12 μg/mL against promastigotes, and 6.16- 40.12 μg/mL against amastigotes of both Leishmania species. They showed moderate cytotoxicity against Vero cell lines and peritoneal mice macrophages, with CC50 values of 100- 500 μg/mL, but > 1600 μg/mL against red blood cells. Selectivity indices ranged from 7.97 to 30.97. The crude extract, and its ethyl acetate and hexane fractions possessed 54.78- 127.72 mg of gallic acid equivalent TPC, 18.30- 79.21 mg of quercetin equivalent TFC, and 27.62- 97.22 mg of atropine equivalent TAC per gram of extracts.Conclusion: The seeds of the plant possessed anti-leishmanial activities against L. aethiopica and L. donovani that might provide a scientific justification for its use in the treatment of leishmaniasis by traditional healers. Future works are recommended to isolate, purify and identify the possible secondary metabolites attributed to the anti-leishmanial activity.Keywords: anti-leishmanial activity, Brucea antidysenterica seeds, Leishmania aethiopica, Leishmania donovani, promastigote, amastigote